MEKANISME PEMAKZULAN PRESIDEN SEBAGAI PENGUATAN SISTEM PRESIDENSIAL DI INDONESIA - Parasatya, Idea Islami; Supryadi, Ady (Jurnal Muhakkamah, 2019)
The dynamic state administration shows the relationship between law and politics in the process of dismissing the president as head of state. The 1945 Constitution of the Republic of Indonesia as a result of the amendment specifically contained the provisions concerning the dismissal of the president as head of state. Amendments to the 1945 Constitution of the Republic of Indonesia determine in more detail the reasons and mechanisms for the impeachment of the president as stipulated in Article 7A and Article 7B of the 1945 Constitution of the Republic of Indonesia. The regulation regarding presidential impeachment in the constitution is the right thing and very in accordance with the principles of the rule of law and democracy, and is a logical consequence when wanting to realize a stable government in accordance with the practice of presidential government systems.